Abscisic acid induces biosynthesis of bisbibenzyls and tolerance to UV-C in the liverwort Marchantia polymorpha. (September 2015) - Kageyama, Akito; Ishizaki, Kimitsune; Kohchi, Takayuki; Matsuura, Hideyuki; Takahashi, Kosaku
Abstract : Graphical abstract: ABA and UV-C induced the biosynthesis of bisbibenzyls in the model liverwort Marchantia polymorpha, and UV-C irradiation was severely damaging to the MpABI1 overexpressor. Highlights: ABA induces the biosynthesis of bisbibenzyls in Marchantia polymorpha . UV-C irradiation increased ABA levels in M. polymorpha . Suppression of ABA signaling inhibited the biosynthesis of bisbibenzyls. UV-C irradiation severely damaged the MpABI1 overexpressor. The plant hormone is suggested to regulate secondary metabolism in land plants. Abstract: Environmental stresses are effective triggers for the biosynthesis of various secondary metabolites in plants, and phytohormones such as jasmonic acid and abscisic acid are known to mediate such responses in flowering plants. However, the detailed mechanism underlying the regulation of secondary metabolism in bryophytes remains unclear. In this study, the induction mechanism of secondary metabolites in the model liverwort Marchantia polymorpha was investigated. Abscisic acid (ABA) and ultraviolet irradiation (UV-C) were found to induce the biosynthesis of isoriccardin C, marchantin C, and riccardin F, which are categorized as bisbibenzyls, characteristic metabolites of liverworts. UV-C led to the significant accumulation of ABA . Overexpression of MpABI1, which encodes protein phosphatase 2C (PP2C) as a negative regulator of ABA signaling, suppressed accumulation of bisbibenzyls in response to ABA and UV-C irradiation and conferred susceptibility to UV-C irradiation. These data show that ABA plays a significant role in the induction of bisbibenzyl biosynthesis, which might confer tolerance against UV-C irradiation in M. polymorpha .